Antimicrobial activity of lactic acid bacteria against pathogens causing food borne diseases - Datta, Dipanjana (BRAC University, 2017)
This Thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2016.